2014
DOI: 10.1016/j.vaccine.2014.04.080
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Universal Immunization Programme and introduction of a rotavirus vaccine in India with IndiaSim

Abstract: Improving immunization coverage and the introduction of a rotavirus vaccine significantly alleviates disease and financial burden in Indian households. Population subgroups or regions with low existing immunization coverage benefit the most from the intervention. Increasing coverage by targeting those subgroups alleviates the burden more than simply increasing coverage in the population at large.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 19 publications
0
46
0
Order By: Relevance
“…13 Vaccines could also reduce the number of people who fall into poverty due to a catastrophic medical expense which is defined as a large proportion (typically, more than 10% to 25%) of household income or expenditure. 12,[14][15][16][17][18][19][20] The protection which vaccines provide against the financial risk from a large medical expense can be measured in additional ways. The so-called extended cost-effectiveness (ECEA) studies have estimated large money-metric value of insurance provided by vaccines.…”
Section: Economic Equity and Global Health Benefits Of Vaccinesmentioning
confidence: 99%
“…13 Vaccines could also reduce the number of people who fall into poverty due to a catastrophic medical expense which is defined as a large proportion (typically, more than 10% to 25%) of household income or expenditure. 12,[14][15][16][17][18][19][20] The protection which vaccines provide against the financial risk from a large medical expense can be measured in additional ways. The so-called extended cost-effectiveness (ECEA) studies have estimated large money-metric value of insurance provided by vaccines.…”
Section: Economic Equity and Global Health Benefits Of Vaccinesmentioning
confidence: 99%
“…The Disease Control Priorities Project 3rd edition (DCP3), which contains an up-to-date comprehensive review of the cost effectiveness of priority health interventions with the special focus on low-and middle-income countries, includes contributions from a significant number of Indian researchers. Also, some of the economic evaluations being included under this project are based purely on Indian perspective [142][143][144]. Thus, DCP3 has also stimulated further interest among researchers doing economic evaluation of health interventions in India, as well as advocacy for use of such evidence by policy makers.…”
Section: Recent Policy Developments In Indiamentioning
confidence: 99%
“…38 In view of this, scaling up of routine immunisation and improved coverage of routine immunisation will increase opportunity to provide rotavirus vaccine to maximum number of children. 39 Concerns about safety of rotavirus vaccine and its association with intussusception was expressed by health care providers and parents in few studies probably in view of withdrawal of first Rotavirus vaccine in US. 16,19,14 Post-marketing studies on the newer vaccines have shown favourable risk benefit ratio of introduction of the vaccine in routine vaccination.…”
Section: Discussionmentioning
confidence: 99%